PENGEMBANGAN SUMBER DAYA INSANI - Yustina PritaAndini (The Center for Research and Community Service of Islamic Institute of Hasanuddin Pare-Kediri, 2020)
The development of human resources is essentially one of the elements of human development. Notoatmojo provides a macro definition of human resource development as a process of improving human quality or ability in order to achieve national development goals. This improvement process includes planning, developing and managing human resources, while micro human resource development is a process of planning education, training and management of personnel or employees to achieve an optimal result. The study of human resource development is a very interesting study because every human era is required to develop. In sharia, human resource development consists of training in skills, knowledge, behavior and sharia competence. Indonesia has tremendous potential to develop the halal industry. These potentials include the abundant Muslim population which is projected to reach 256 million in 2050, the growth of various halal industry sectors, especially the financial, tourism and fashion sectors, the recognition of Indonesia's achievements in the eyes of the world, Indonesia's geographical conditions and demographic bonuses, technological developments , as well as ratification of the Halal Product Guarantee Law number 33 of 2014.